Performance Optimization of the General Criminal Investigation Unit to Overcome Motorcycle Theft in Order to Uphold Fair Law Enforcement in Polresta Surakarta - Dania Sumarto (Akademi Kepolisian Republik Indonesia, 2023)
Thievery is becoming the highest incidence on criminal cases in Indonesia up to December 2022. Surakarta is the most populated city in Central Java. Highly densed population together with many activities on the region caused a rising diversity of problems of economic, cultural, politic, and public security. According to the Statitical Bureau (BPS) of Central Java on the year of 2021, Surakarta is ranked the second highest criminal cases in Central Java. The most common crimes in Surakarta is thievery. Motorcycle thievery in Surakarta is due to its economic value and highly used transportation in Surakarta. Police criminal Investigation unit whom bear the task to overcome motorcycle theft is General Investigation unit (Resum). This research is aim to identify and to describe the management application and competency on general criminal investigation unit police officers in order to overcome motorcycle theft. Several problems occured such as impairment on technology, officers’ quantity and quality, impairment on facilities, thief whos still in quest or recidivist, lack of supervision, and the inability to set standard operational procedure when on duty to reveal the theft. A number of solutions and innovations related to the problems found are to have collaboration with another institution like Dukcapil, Dishub, Universities, and local goverment of Surakarta. This study is hoped to be able to help enforcing the law in this institution. Moreover, this can be added as suggestions to the higher leader to make a better policy for Polresta Surakarta.